2009
DOI: 10.4314/ijbcs.v2i4.39766
|View full text |Cite
|
Sign up to set email alerts
|

CNS activity of ZS-1A: a phytoceutical from <i>Zizyphus spina-christi</i> root bark

Abstract: Zizyphus spina-christi (ZS) Willd is reputed to have medicinal values. Studies on the phytochemistry, and some pharmacological activity of the plant's rootbark were initiated in our laboratories. The present study is a report on sedative effect of a fraction obtained from the hexane extract (numbered ZS-1A) of the plant material. The fraction (25, 50 and 100 mg/kg, p.o.) were tested against pentobarbital sleeping time, motor coordination (rota-rod performance) test and exploratory behaviour in mice. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The fruits are applied on cuts and ulcers. They are also used to treat pulmonary ailments and fevers and to promote the healing of fresh wounds, for dysentery (Adzu et al, 2001). The leaves are applied locally to sores, and the roots are used to cure and prevent skin diseases (Adzu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruits are applied on cuts and ulcers. They are also used to treat pulmonary ailments and fevers and to promote the healing of fresh wounds, for dysentery (Adzu et al, 2001). The leaves are applied locally to sores, and the roots are used to cure and prevent skin diseases (Adzu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They are also used to treat pulmonary ailments and fevers and to promote the healing of fresh wounds, for dysentery (Adzu et al, 2001). The leaves are applied locally to sores, and the roots are used to cure and prevent skin diseases (Adzu et al, 2001). The seeds are sedative and are taken sometime with buttermilk to halt nausea, vomiting and abdominal pains associated with pregnancy (Kaaria, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous root bark extract of Z. spina christi (25–100 ml/ kg) and the LD 50 of the fraction was 871.78 mg/kg for intraperitoneal were administered to the Swiss mice. This study revealed that doses (25, 50 and 100 mg/kg) were within the safe limit ( Adzu et al, 2009 ). A study was conducted to investigate the toxicity of six plants in the traditional Arab system of medicine.…”
Section: Toxicological Effectsmentioning
confidence: 67%
“…Ziziphus nummularia was not found to exhibit any behavioral changes or mortality in mice administered with aqueous-methanol Ziziphus nummularia leaf extract at oral doses of 3 and 5 g/kg, and up to 10 g/kg in a 24-h study, suggesting that Ziziphus nummularia is safe to use, and making it an attractive plant for natural drug discovery approaches [10]. In addition, toxicity analysis of other Ziziphus species concluded that they were safe [106,107]. Nonetheless, although toxicity studies indicate that Ziziphus nummularia extracts are nontoxic, there is still a need for further toxicology screening and particularly for long-term chronic toxicity studies to validate their safe usage.…”
Section: Toxicology Studiesmentioning
confidence: 99%